Kualitas Soal Penilaian Akhir Semester (PAS) Buatan Guru Mata Pelajaran Kimia Kelas XI MIA SMA Di Kabupaten Kotawaringin Barat Pada Semester Ganjil Tahun Ajaran 2018/2019 - Yesi Gasela; Suandi Sidauruk; Abdul Hadjranul Fatah (FKIP Universitas Palangka Raya, 2020)
The questions used in the Final Semester Assessment are teacher-made questions. This study aims to determine and describe the level of Quality of Final Semester Assessment Questions Made by Chemistry Subject Teachers in Class XI MIA Senior High School in Kotawaringin Barat District in Odd Semester Academic Year 2018/2019. This research is a descriptive study. The objects in this study were questions made by the teacher and students' answers from the Final Semester Assessment Chemistry subjects in class XI MIA High School A, class XI MIA High School B, class XI MIA High School C, and Class XI MIA High School D, in the odd semester of the year 2018/2019 teachings. The research data collection technique is the documentation method. Data analysis was performed by logical review and empirical review. The results showed that the results of the logical review analysis obtained the level of concordance with the basic competencies classified as good with a percentage of 86.67%. Judging from the aspects of material, construction, and language the level of appropriateness of the questions is good with a percentage of 85.63%. The distribution of Bloom's cognitive taxonomic domains is C1 at 22.67%, C2 at 43.33%, C3 at 34%, C4 at 0%, C5 at 0%, and C6 at 0%. The quality of the chemistry PAS questions for class XI MIA made by the teacher in terms of empirical review was obtained based on the different power index, difficulty index and distractor effectiveness. Empirical review, the number of questions with very good quality there are 35 (23.33%) questions, questions with good quality there are 55 (36.67%) questions, questions with not good quality there are 57 (38%) questions, and questions with the quality is not very good there are 3 (2%) questions.